2018
DOI: 10.1002/biot.201800211
|View full text |Cite
|
Sign up to set email alerts
|

Structural Features on the Substrate-Binding Surface of Fungal Lytic Polysaccharide Monooxygenases Determine Their Oxidative Regioselectivity

Abstract: Lytic polysaccharide monooxygenases (LPMOs) are copper-dependent enzymes that oxidatively cleave many of nature's most recalcitrant polysaccharides by acting on the C1-and/or C4-carbon of the glycosidic bond. Here, the results of an extensive mutagenesis study on three LPMO representatives, Phanerochaete chrysosporium LPMO9D (C1-oxidizer), Neurospora crassa LPMO9C (C4), and Hypocrea jecorina LPMO9A (C1/C4), are reported. Using a previously published indicator diagram, the authors demonstrate that several struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 58 publications
(101 reference statements)
4
49
0
Order By: Relevance
“…Regioselectivity defines whether LPMOs oxidize glucosyl residues in cellulose at the C1 or C4 position, or both [19]. Studies to link sequences and structural features to the regioselectivity of LPMO have been attempted [19][20][21][22][23][24][25][26][27][28][29][30]. So far, although similarities have occurred, such phylogenetic analysis could not unambiguously predict the three LPMO regioselectivities.…”
Section: Introductionmentioning
confidence: 99%
“…Regioselectivity defines whether LPMOs oxidize glucosyl residues in cellulose at the C1 or C4 position, or both [19]. Studies to link sequences and structural features to the regioselectivity of LPMO have been attempted [19][20][21][22][23][24][25][26][27][28][29][30]. So far, although similarities have occurred, such phylogenetic analysis could not unambiguously predict the three LPMO regioselectivities.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the accessibility of surface-exposed axial position of Cu, or the ability to bind a ligand in the axial position, could be a determinant of C4-oxidizing activity. However, recent studies suggested that, mutations affecting accessibility of this axial position did not change the regioselectivities of PcLPMO9D and MaLPMO10B (Danneels et al 2019;Forsberg et al 2018).…”
Section: Amino Acid Composition and Arrangement On Substrate Binding mentioning
confidence: 92%
“…Therefore, it is speculated that LPMOs may bind to the substrates in different directions, resulting in different regioselectivity (Li et al 2012). Recently, Danneels et al studied the oxidative regioselectivity of LPMO9s in detail (Danneels et al 2019). One part of the research was the mutation of aromatic amino acids on the substrate binding surfaces of PcLPMO9D, ScLPMO9C and HjLPMO9A.…”
Section: Amino Acid Composition and Arrangement On Substrate Binding mentioning
confidence: 99%
See 2 more Smart Citations